Islam, Muslim dan Perilaku Politik - Ida Zahara Adibah (Madaniyah, 2014)
Every individual who is on this earth is inseparable from a country where he is affiliated with him, so he is obliged to respect and even defend him with all his abilities even though he must sacrifice all his body and soul. The concept of a nation state (nation state) is one of the political concepts of a state (state) or community group that is jointly bound by general loyalty and solidarity. This understanding explains the nation state is a territorial entity where the state is as large or coextensive as the nation. The Nation State in the contemporary Islamic world is upheld by a spirit of nationalism or a spirit accompanied by high awareness to build a nation state. The debate about the nation state sounds strange when it is clashed with the ethics of the Qur'an and the historical setting of Islam (Rahman calls it Historical Islam). Historical facts show that throughout the life of the Prophet Muhammad, as concluded by Rahman, the Messenger of Allah was the Ruler of almost the entire Arabian peninsula, but he never called himself a ruler. At that time the term Islamic state (Daulat al-Islam) was not yet known. the charter of Medina is the forerunner to the formation of a Nation State (nation state) and places the Prophet Muhammad not only as a religious leader, but also as a leader of the country. Therefore nationalism in the perspective of classical Islamic repertoire can actually be seen in the formation of the Medina Charter which was carried out by the Prophet Muhammad together with the inhabitants of Medina.